Sitting in the same boat: Subjective well-being and social comparison after an extreme weather event - Kati Krähnert; Svenja Fluhrer (ZBW - Leibniz Information Centre for Economics, 2021)
How does subjective well-being depend on the fate of others when a covariate shock strikes? In this paper, we address this question by providing novel evidence on the impact of shock-induced damages experienced by individuals and their reference group on life satisfaction. We do so by examining the case of pastoralists in Mongolia that faced a oncein-50-years winter disaster. Our identification strategy exploits the quasi-experimental nature of the extreme event. The empirical analysis builds on a detailed household panel survey, which we complement with aggregated climate data and historic livestock census data. Results show that exposure to the extreme event significantly and strongly reduces subjective well-being even 4-5 years after the event occurred. The negative shock impact is amplified by observing peers doing economically worse. Similarly, exposure to the extreme event increases the perceived inequality among households with assets at risk. We argue that the event increases sectoral disparities between pastoralists and households not engaged in agriculture.
Keywords: I30; D63; O13; O15; Q54; 330; extreme weather event; pastoralism; self-reported shock; socialcomparison; subjective well-being